Investigating the Role of Conceptual Metaphor in the Representation of the Syrian Human Crisis in British Newspaper Articles: A Cognitive Approach - Saadeya Elsayed Salem; Nihad M. Mansour; Inas H. Hassan; Riham A. Debian (Journal of Language and Literature, 2022)
This paper investigates the representation of the Syrian human crisis through the conceptual metaphor of the “Other”. It particularly examines how conceptual metaphor plays a role in the representation of the Syrian human crisis in British Newspaper Articles. It also highlights the use of “Us” vs. “Them” dichotomy in the representation of both groups in the selected newspaper articles. Utilizing Lakoff and Johnson’s (1980) Conceptual Metaphor Theory (CMT) and cross-domain mapping, along with Van Dijk’s (1995) Ideological Square (IS), the paper examines the use of conventionalized and novel conceptual metaphors in the representation of the Syrian human crisis in British newspaper articles. 100 newspaper articles about the crisis are collected from three British newspapers (The Guardian, The Daily Mail and the Daily Telegraph) between 2014 and 2016. The paper concludes with a discussion of how these newspapers make use of conceptual metaphor to portray Syrian refugees as THREAT, OBJECTS, WATER, ANIMALS and ILLNESS/DISEASE. Moreover, the use of “Us” vs. “Them” dichotomy indicates social distance and contributes to the representation of Syrian refugees as the “Other”. Words like “immigrants” and “asylum seekers” are also used in addition to “refugees” to refer to Syrians. The oscillation between these labels highlights the strategy mainstream media follows to strip Syrian refugees from the official rights identified by the United Nations.